Interest-Free Deficit Financing: Rejoinder - Poindexter, J. Carl (Quarterly Journal of Economics, 1945)
Journal Article Interest-Free Deficit Financing: Rejoinder Get access J. Carl Poindexter J. Carl Poindexter Roanoke College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 60, Issue 1, November 1945, Pages 154–165, https://doi.org/10.2307/1880647 Published: 01 November 1945